Market Structure, Efficiency and Profitability: An Empirical Study on the Chinese Banking Industry 2007-2012 - Che, Chang (2014)
Since the economic reform was initiated in 1978, the Chinese banking sector has undergone significant changes, especially after the entry to the WTO in 2001 and shock by the global financial crisis in 2008.